Logic Oughtn't be Normative - Searle, Christopher J. (Array, 2021)
Presumably, the exponent of logical normativity believes it to be the case that rational agents ought to reason logically. If the converse holds, and the exponent of logical normativity believes either (a) that it is false that rational agents ought to reason logically or (b) that the claim that rational agents ought to reason logically is not truth–functional, then any attempt to formulate sound arguments in support of their position will be either question–begging or self–contradictory. To argue in favour of the normative status of logic involves the assumption that the issue is substantive. I draw a distinction between deontic and axiological normativity as applied to logical theory and demonstrate that because deontic sentences are not truth–functional, logic cannot be normative in the deontic sense. I conclude that the only sense in which logical theory may be thought of as normative is axiologically.